Effect of Addition Turmeric Powder (Curcuma domestica) on the Beef Patty: Physicochemical Properties and Microbial Profile - Aprini, Gita; Kirana, Fiala Lokarita; Mubarok, Fajar (Jurnal Ilmu dan Teknologi Hasil Ternak, 2026)
The purpose of this study was to determine the effect of turmeric powder addition on physicochemical properties and microbial profile of beef patty. The method used was a completely randomised design (CRD) consisting of 4 treatments with 4 replicates. The research treatments with the use of turmeric powder were P0 as a control treatment without the addition of turmeric powder, P1 (0.5 %), P2 (1 %), P3 (1.5 %). The result showed that the additions of turmeric powder (Curcuma domestica) did not gave significant effect (p < 0.05) on WHC, fat content, moisture content, water activity (Aw), color L* and a* of the beef patties, TPC and Mold, WHC with an average (55.04-56.72%), fat content (3.95-4.32%), moisture content (60.2819-61.5104%), Aw (0.9480-0.9488), color L* (37.27-39.66), color a* (13.39-18.56), TPC (6.0095-7.0878 CFU/g), and mold (1.4039 ± 0.3065 log CFU/g). The result showed that the additions of turmeric powder have a significant effect (p < 0.05) on pH, with an average pH (5.92-6.02). The result showed that the additions of turmeric powder were highly significant effect (p < 0.01) on yeast and color b* of beef patties, with an average yeast (1.4771-2.9790 CFU/g), color b* 21.84-29.25. The addition of turmeric powder can stabilize the physicochemical properties and microbial profile of beef patty.